The Belarusian Orthodox Church at grassroots’ level: the organisation, functioning and role of Orthodox brotherhoods and sisterhoods in Belarus - Mudrov, Sergei A.; Zakharov, Nikolay V. (Journal of the Belarusian State University. Sociology, 2021)
This article is devoted to the analysis of the growing importance of brotherhoods and sisterhoods of the Belarusian Orthodox Church. Currently these organisations perform important social, educational, informational and charitable functions, up to and including at regional level. This article analyses how the conditions and the logic of their operation are dependent on local religious contexts and how they are inscribed in the broader context of the growing role of the church in emerging community welfare in contemporary Belarus. In this article, special attention is given to the analysis of activities of the Union of Sisterhoods and the sisterhoods in Lida and Novogrudok. These sisterhoods mainly work to achieve important social and charitable objectives. In the case of brotherhoods, their main activities have been confined to educational and missionary work, as seen in the example of the Three Martyrs of Vilna brotherhood in Minsk.
Keywords: church; Orthodoxy; Belarus; brotherhoods; sisterhoods; charities; welfare state; civil society